A Novel Magnetosphere–Ionosphere Coupling Model for the Onset of Substrom Expansion Phase - Wang, P. S.; Lyu, L. H. (Frontiers in Astronomy and Space Sciences, 2021)
A novel magnetosphere-ionosphere (M-I) coupling model is proposed to simulate the brightening of the onset auroral arc of a magnetospheric substorm event. The new M-I coupling model is modified from the M-I coupling model proposed by the Alaska research team in 1988. We adjust the magnetospheric boundary conditions by including the Hall effects in the thin current sheet and allowing the spatial distributions of the reflection-transmission coefficient to vary with time. As a result, brightening and poleward drifting of multiple auroral arcs appear for the first time in an M-I coupling model. The new results indicate that the coupled Hall effects in the near-Earth plasma sheet and the E-region ionosphere play a vital role in triggering the onset of a magnetospheric substorm